Caregivers’ Considerations of Remorse and Responsibility Among Youth Who Sexually Offend - Gervais, Christine L. M. (Journal of interpersonal violence, 2022)
When a youth sexually offends, most of the reactions and repercussions that follow are understandably negative. However, there is limited research about mixed reactions involving remorse and responsibility on the part of the adolescent who offended and their relatives. Based on qualitative interviews with 16 caregivers among 10 families in Canada, this article presents the parents? perspectives on the various processes, benefits, challenges, and outcomes related to expressions of remorse and experiences of responsibility among youth who sexually offended, their victims, and their parents. This study sheds particular light on how adolescent perpetrators of sexual harm and especially their caregivers do feel deeply remorseful and responsible for the impacts of sexual offending behavior, which is contrary to public scrutiny that negatively projects responsibility onto youth offenders and their parents. Thus, our findings emphasize the constructive and considerate ways in which remorse is felt and responsibility is assumed; and by extension, they point to the importance of restorative practices in efforts toward reconciliation and accountability.